Peculiarities of the first aid to patients with orbital injuries (Ukrainian Journal of Ophthalmology, 2026)
The importance of this study is due to increased frequency of the middle facial zone fractures involving orbital injuries. Aim. To increase the treatment effectiveness of patients with injuries of the middle facial zone, combined with orbital injuries by improving methods for restoration of anatomic integrity and additional eye apparatus. Materials and methods. There were treated 157 patients with orbital injuries, the principles of an integrated approach to treatment and rehabilitation of patients were presented. A comparative analysis using bioresorptive polymer and titanium plates for osteosynthesis of fractures based on biomechanicss was performed. Results. 1) the frequency of fractures of the middle zone face increased to 26.3 %; 2) these damages are accompanied by changes in the volume of the orbit, which can lead to aesthetic, functional impairment due to displacement of the eyeball and injuries of the eye additional apparatus; 3) in the treatment of the middle facial zone fractures bioresorptive polymer plates with screws for osteosynthesis should be used that do not require their further removal; 4) restoration of the lacrimation in total lacrimal ducts is possible using autograft from the cheek mucosa.
Keywords: damage of the orbit; midface fractures; bioresorbed polymer plates